Implementation of Creative Problem Solving Model to Improve Students' Critical Thinking Skills in Chemistry Lessons - Muzaimah Muzaimah; Abdul Gani; Andi Ulfa Tenri Pada; Ratu Fazlia Inda Rahmayani; Muhammad Syukri; Yusrizal Yusrizal (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Implementation of the 2013 and prototype curriculum requires students to master critical thinking skills. This study aims to determine differences improvement of students' critical thinking skills who were taught using Creative Problem Solving (CPS) and direct learning model in chemistry learning. This research is quasi-experimental research. The research sample was 64 student from class 10th grade, which are 32 students in experimental class and 32 students in control class. The sample was taken by purposive sampling. The instrument used is critical thinking skills test consisting of 15 questions. Data collection was carried out pretest and posttest. Data analysis used N-gain test and independent sample t-test. The results showed that the experimental class's average N-gain of critical thinking skills was 0.84 (high) and the control class was 0.61 (medium). There are differences in students' critical thinking skills taught with CPS and direct learning model. The difference in the highest increase is found in the inference indicator which only exists in the CPS learning model. This proves that the application of the CPS model affects critical thinking skills better than the direct learning model.